More ways to explore the translating mind: Collaborative translation protocols. - Pavlović, Nataša (2009)
Investigation of translation processes has intensified over the past two decades largely due to the application of the introspective verbal reporting method known as think aloud (thinking aloud). In this paper, a less widely used method of research into translation processes is examined: the collaborative translation protocol (CTP). References are also made to integrated problem and decision reporting (IPDR) and choice network analysis (CNA). The paper reviews the main issues concerning CTP, reporting on the author’s experiences in using the method to investigate translation processes.
ENG